Dandelion Optimizer algorithm-based method for accurate photovoltaic model parameter identification - Elhammoudy, Abdelfattah; Elyaqouti, Mustapha; Arjdal, El Hanafi; Ben Hmamou, Dris; Lidaighbi, Souad; Saadaoui, Driss; Choulli, Imade; Abazine, Ismail (Energy conversion and management. X, 2023)
•A novel algorithm DONR is proposed for identifying parameters of SDM and DDM.•A novel contribution to the literature is the utilization of a numerical method for calculating the objective function.•The DONR is compared with state-of-the-art algorithms using benchmark I-V and P-V data.•Results show that the proposed method outperforms all other methods. The utilization of photovoltaic (PV) energy has experienced a significant surge in the last few decades, resulting in a rise in research endeavours to comprehend its workings better. One of the focal points of this research is the electrical modelling of PV cells and modules. Several equivalent circuits have been proposed to model them, such as the single-diode (SDM), double-diode (DDM), and triple-diode model (TDM). The main challenge is identifying the optimal circuit model parameters. This study introduces a novel method based on a metaheuristic algorithm named Dandelion Optimizer (DO) coupled with a numerical method Newton-Raphson (NR) to estimate the PV parameters. Various PV models, including the single-diode model (SDM) and double-diode model (DDM), were utilized by the proposed method (DONR) to determine the PV parameters of six different cells and modules, such as RTC France, Photowatt-PWP201, and STP6-120/36. A comparative analysis was conducted with ten other widely recognized metaheuristic methods to demonstrate the effectiveness of the proposed method. The results demonstrate that the proposed algorithm is more accurate in estimating the optimal PV parameters than the other methods. According to the experimental results, the proposed method is superior to other methods in accurately estimating the optimal PV parameters in terms of accuracy, reliability, and convergence. Specifically, the root mean squared error values obtained by the proposed method using (SDM, DDM) for RTC France, PWP201, and STP6-120/36 are (7.73939E-04, 7.56515E-04), (2.08116E-03, 2.07842E-03) and (1.42575E-02, 1.45952E-02), respectively.